Elementary schoolers' attitudes toward reading in English: how boys feel relative to girls - Mohd. Asraf, Ratnawati; Abdullah, Hazlina (Canadian Center of Science and Education, 2016)
This paper describes the results of a study that examined the attitudes of Malaysian primary school boys and girls toward reading in English as a Second Language. Using the Students’ Reading Attitude Survey, which the researchers adapted from McKenna and Kear (1990) Elementary Reading Attitude Survey, 2,666 responses were analysed using the non-parametric Mann-Whitney U test.